Twist induces epithelial-mesenchymal transition and cell motility in breast cancer via ITGB1-FAK/ILK signaling axis and its associated downstream network. (February 2016) - Yang, Jiajia; Hou, Yixuan; Zhou, Mingli; Wen, Siyang; Zhou, Jian; Xu, Liyun; Tang, Xi; Du, Yan-e; Hu, Ping; Liu, Manran
Abstract: Twist, a highly conserved basic Helix-Loop-Helix transcription factor, functions as a major regulator of epithelial-mesenchymal transition (EMT) and tumor metastasis. In different cell models, signaling pathways such as TGF-β, MAPK/ERK, WNT, AKT, JAK/STAT, Notch, and P53 have also been shown to play key roles in the EMT process, yet little is known about the signaling pathways regulated by Twist in tumor cells. Using iTRAQ-labeling combined with 2D LC–MS/MS analysis, we identified 194 proteins with significant changes of expression in MCF10A-Twist cells. These proteins reportedly play roles in EMT, cell junction organization, cell adhesion, and cell migration and invasion. ECM–receptor interaction, MAPK, PI3K/AKT, P53 and WNT signaling were found to be aberrantly activated in MCF10A-Twist cells. Ingenuity Pathways Analysis showed that integrin β1 (ITGB1) acts as a core regulator in linking integrin-linked kinase (ILK), Focal-adhesion kinase (FAK), MAPK/ERK, PI3K/AKT, and WNT signaling. Increased Twist and ITGB1 are associated with breast tumor progression. Twist transcriptionally regulates ITGB1 expression. Over-expression of ITGB1 or Twist in MCF10A led to EMT, activation of FAK/ILK, MAPK/ERK, PI3K/AKT, and WNT signaling. Knockdown of Twist or ITGB1 in BT549 and Hs578T cells decreased activity of FAK, ILK, and their downstream signaling, thus specifically impeding EMT and cell invasion. Knocking down ILK or inhibiting FAK, MAPK/ERK, or PI3K/AKT signaling also suppressed Twist-driven EMT and cell invasion. Thus, the Twist-ITGB1-FAK/ILK pathway and their downstream signaling network dictate the Twist-induced EMT process in human mammary epithelial cells and breast cancer cells.